A matemática escolar e o ENEM (1998-2002): o aparecimento de uma nova vulgata? - Paiva, Manoel Rodrigues (2003)
This work is the result of a research about the influence of the ENEM (High School National Exam) from 1998 to 2002 in the Mathematic didactic book for high school level and, simultaneously, in the Mathematic discipline in Brazil. Starting from a global context the guidelines of the new directions of the Brazilian high school education are presented. Several ideas of competence notion have been discussed and the ENEM has been presented with its theoretical basis and guidelines, pointing out the skills and competence evaluated by the ENEM, with the objective to establish a counterpoint to the official documents, some criticism to the ENEM exam has been presented from specialists in education, Mathematics and cognitive psychology. To investigate the possible changes in the Mathematic discipline, two didactic books prior to 1998 and two after 2002 were analyzed under the prospective of competence and skills from the ENEM. This analysis showed that the didactic book registered the beginning of a transformation movement in the Mathematic discipline, motivated, as everything indicates, by the new guidelines proposed at the National Curriculum Standards for High School (PCNEM), which were based on the results at the International Meeting of Education for the XXI century of the United Nations Educational, Scientific and Cultural Organization (UNESCO). The ENEM, as the first official document to make these proposals concrete as exercises, seems to become a reference